2005
DOI: 10.1021/bi047721l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant Long-Chain Rat Acyl-CoA Synthetase Isoforms 3 and 6:  Identification of a Novel Variant of Isoform 6

Abstract: The metabolism of long-chain fatty acids in brain and their incorporation into signaling molecules such as diacylglycerol and LPA and into structural components of membranes, including myelin, requires activation by long-chain acyl-CoA synthetase (ACSL). Because ACSL3 and ACSL6 are the predominant ACSL isoforms in brain, we cloned and characterized these isoforms from rat brain and identified a novel ACSL6 clone (ACSL6_v2). ACSL6_v2 and the previously reported ACSL6_v1 represent splice variants that include ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
154
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(167 citation statements)
references
References 30 publications
12
154
1
Order By: Relevance
“…On the other hand, we demonstrated a 32% reduction in brain microsomal acyl-CoA synthetase activity (Vmax) in preparations from α-synuclein deficient mouse brains ( Figure 5 and Table 3). In addition, the Vmax/Km ratio was also significantly depressed in the gene-ablated mice (Table 3), demonstrating that under physiological conditions (75) there would be an effect by α-synuclein on Acsl activity. While we demonstrated the presence of α-synuclen in snca +/+-microsomes (Figure 6), others have also noted that α-synuclein is particularly enriched in microsomal fractions containing primarily ER (23) as well as colocalized with ER in synaptosomal preparations (21,80,89), but not found associated with synaptic vesicles (80).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, we demonstrated a 32% reduction in brain microsomal acyl-CoA synthetase activity (Vmax) in preparations from α-synuclein deficient mouse brains ( Figure 5 and Table 3). In addition, the Vmax/Km ratio was also significantly depressed in the gene-ablated mice (Table 3), demonstrating that under physiological conditions (75) there would be an effect by α-synuclein on Acsl activity. While we demonstrated the presence of α-synuclen in snca +/+-microsomes (Figure 6), others have also noted that α-synuclein is particularly enriched in microsomal fractions containing primarily ER (23) as well as colocalized with ER in synaptosomal preparations (21,80,89), but not found associated with synaptic vesicles (80).…”
Section: Discussionmentioning
confidence: 90%
“…Kinetics assays show that this isoform has conspicuously different ATP-binding affinities (29). A further locus for which there is evidence of distinct functions is XX-FW83563B9.3 (TAZ), where it has been shown that alternative isoform 002, which has a 31-residue deletion from skipping the fifth exon, may in fact be the principal isoform, because it is the only isoform to have full cardiolipin metabolic activity (30).…”
Section: Resultsmentioning
confidence: 99%
“…Based upon these data, it has been predicted that ACSL3 has an active role in phospholipid or eicosanoid metabolism (36). ACSL3 has a broad range of substrate preferences toward C 16 -C 24 fatty acids (35,37). Although few studies have focused on the physiological function of ACSL3 (16,35), its localization on lipid droplets or endoplasmic reticulum membranes (31,32) suggests that this enzyme is likely involved in lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%